Tell Me a Story: Socio-Emotional Functioning, Well-Being and Problematic Smartphone Use in Adolescents With Specific Learning Disabilities - Sarti, Daniela; Bettoni, Roberta; Offredi, Ilaria; Tironi, Marta; Lombardi, Elisabetta; Traficante, Daniela; Lorusso, Maria Luisa (Frontiers in Psychology, 2019)
Although Specific Learning Disabilities (SLD) are described as specific difficulties in one or more academic areas, often socio-emotional problems are also reported having cascading effects on well-being and school engagement. Moreover, emotional problems and reduced social support were found to predict problematic use of new technologies, like a smartphone, which can, in turn, increase these problems. Here, we aimed to investigate socio-emotional functioning in adolescents with and without a diagnosis of SLD and its relations with well-being, school engagement, and problematic smartphone use. Social and emotional skills were assessed through a narrative test; adolescents were requested to narrate complete stories elicited by pictures representing social situations. Information on well-being and problematic smartphone use were collected by questionnaires. The comparison between groups showed differences in cognitive-social skills, while, no significant differences in emotional functioning were found. Additionally, the perception of the social environment as supportive and trustworthy was related to general well-being for both groups, whereas, the perception of limits and rules setting by the adult world appeared to be related to a decreased investment in learning processes only for the SLD students. Finally, correlation analysis showed that smartphone use was associated with reduced perception of social support and also to a decreased ability to understand and solve social situations. These results assert the critical role played by social information processing and social support in terms of well-being in adolescence, and they contribute to enhancing knowledge of the mechanisms underlying problematic smartphone use also in a clinical sample.